Preliminary Definitions for the Sonographic Features of Synovitis in Children - Roth, Johannes; Ravagnani, Viviana; Backhaus, Marina; Balint, Peter; Bruns, Alessandra; Bruyn, George A.; Collado, Paz; De la Cruz, Lorenia; Guillaume Czitrom, Severine; Herlin, Troels; Hernández, Cristina; Iagnocco, Annamaria; et al. (American College of Rheumatology, 2017)
Objective. Musculoskeletal ultrasonography (US) has the potential to be an important tool in the assessment of disease activity inchildhood arthritides. To assesspathology,clear deﬁnitionsforsynovitisneed tobedeveloped ﬁrst. The aim of thisstudy was to develop and validate these deﬁnitions through an international consensus process. Methods. The decision on which US techniques to use and the components to be included in the deﬁnitions, as well as the ﬁnal wording, were developed by 31 US experts in a consensus process. A Likert scale of 1–5 (where 15complete disagreement and 55complete agreement) was used. A minimum of 80% of the experts scoring 4 or 5 was required for ﬁnal approval. The deﬁnitions were then validated on 120 standardized US images of the wrist, metacarpophalangeal joints, and tibiotalar joints, displaying various degrees of synovitis at various ages. Results. B-mode and Doppler should be used for assessing synovitis in children. A US deﬁnition of the various components (i.e., synovial hypertrophy, effusion, and Doppler signal within the synovium) was developed. The deﬁnition was validated on still images with a median of 89% of participants (range 80–100) scoring it as 4 or 5 on a Likert scale. Conclusion. US deﬁnitions of synovitis and its elementary components covering the entire pediatric age range were successfully developed through a Delphi process and validated in a web-based still-images exercise. These results provide the basis for the standardized US assessment of synovitis in clinical practice and research.